The Protection of Salidroside of the Heart against Acute Exhaustive Injury and Molecular Mechanism in Rat - Wang, Yunru (Hindawi Publishing Corporation, 2013)
Objective. To investigate the protection of salidroside of the heart against acute exhaustive injury and its mechanism of antioxidative stress and MAPKs signal transduction. Method. Adult male SD rats were divided into four groups randomly. Cardiomyocytes ultrastructure was observed by optical microscopy and transmission electron microscopy. The contents of CK, CK-MB, LDH, MDA, and SOD were determined by ELISA method, and the phosphorylation degrees of ERK and p38 MAPK were assayed by Western blotting. Cardiac function of isolated rat heart ischemia/reperfusion was detected by Langendorff technique. Results. Salidroside reduced the myocardium ultrastructure injury caused by exhaustive swimming, decreased the contents of CK, CK-MB, and LDH, improved the LVDP, ±LV dp/dt (max) under the basic condition, reduced the content of MDA and the phosphorylation degree of p38 MAPK, and increased the content of SOD and the phosphorylation degree of ERK in acute exhaustive rats. Conclusion. Salidroside has the protection of the heart against acute exhaustive injury. The cardioprotection is mainly mediated by antioxidative stress and MAPKs signal transduction through reducing the content of MDA, increasing the content of SOD, and increasing p-ERK and decreasing p-p38 protein expressions in rat myocardium, which might be the mechanisms of the cardioprotective effect of salidroside.